Transaminase Elevations during Treatment of Chronic Hepatitis B Infection: Safety Considerations and Role in Achieving Functional Cure - Andrew Vaillant (Viruses, 2021)
While current therapies for chronic HBV infection work well to control viremia and stop the progression of liver disease, the preferred outcome of therapy is the restoration of immune control of HBV infection, allowing therapy to be removed while maintaining effective suppression of infection and reversal of liver damage. This “functional cure” of chronic HBV infection is characterized by the absence of detectable viremia (HBV DNA) and antigenemia (HBsAg) and normal liver function and is the goal of new therapies in development. Functional cure requires removal of the ability of infected cells in the liver to produce the hepatitis B surface antigen. The increased observation of transaminase elevations with new therapies makes understanding the safety and therapeutic impact of these flares an increasingly important issue. This review examines the factors driving the appearance of transaminase elevations during therapy of chronic HBV infection and the interplay of these factors in assessing the safety and beneficial nature of these flares.